A Glance at Evolution of Entrepreneurship and Scope for Entrepreneurship at the BoP (Bottom of the Pyramid) in India - Subhash, Dr. M. S.; A. N., Vijayakumar (Prabandhan: Indian Journal of Management, 2011)
This article discusses two basic aspects - evolution of entrepreneurship concept and the scope of entrepreneurship at the bottom of the pyramid. In the first part, we mainly concentrate and make an effort to add up to the article by Patrick J. Murphy, Jianwen Liao and Harold Welsch. In their article, they have finely discussed regarding the conceptual history of entrepreneurial thought and have come out with an illustration to the conceptual history of entrepreneurial thought. In their work, they have divided the entire history into three parts as three bases - prehistoric bases, economic bases and multidisciplinary bases. In the addition to the above referred work, we felt that there is something missing regarding the importance of the market orientation part in the entrepreneurial concept. Today, in 2010, there is huge potential for those entrepreneurs who like be more market oriented and concentrate more on catering to Niche markets with their specialised products/service offerings. So, we found that the real opportunity for any entrepreneur lies in catering to the demands of the market, being market oriented and having the ability to enhance the value of the customer drives entrepreneurship. In the next part, the article discusses the scope for the entrepreneurship at the bottom of the pyramid. Here, the researchers discuss the works done by C.K. Prahalad, Stuart L. Hart and Aneel Karnani. In their article, the authors C.K. Prahalad and Stuart L. Hart mention that they find a fortune at the bottom of the pyramid and especially for MNCs, it is still an untapped market and the MNCs could extend their services and contribute to the process of poverty alleviation by selling to the poor and bringing them onto the main stream of the society. Whereas the author Aneel Karnani, in his article mentions that there is no fortune at the bottom of the pyramid and the possible way for this problem of poverty alleviation would be to convert them to be producers instead of making them buyers. So, in continuation with the above mentioned aspects, the article will take the readers to know more details on evolution of entrepreneurship concept and the scope for the entrepreneurship at the bottom of the pyramid. As a concluding part, the article will suggest for the improved thoughts on the issues such as entrepreneurship, bottom of the pyramid and poverty alleviation.